Sexual function and reproduction can be impaired in men with rheumatic diseases: A systematic review - Perez Garcia, Luis F.; te Winkel, Bernke; Carrizales, Juan P.; Bramer, Wichor M.; Vorstenbosch, Saskia; Van Puijenbroek, Eugene; Hazes, J.M.W.; Dolhain, R.J.E.M. (2020)
Information about the possible effect of rheumatic diseases on male sexual function and reproduction (sexual health) is scarce and difficult to summarize. Factors known to impair sexual health, such as inflammation, medication use and hypogonadism can be present in a significant proportion of male patients with rheumatic diseases. Objectives: The objective of our study was to systematically review the literature for the influence of paternal rheumatic disease on sexual health, such as sexual function, reproductive hormones, male fertility, pregnancy and offspring outcomes. Data sources: English language articles identified through Embase, MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, Google Scholar and the Clinical trial registries of Europe and the USA published until February 2019. Study appraisal and synthesis methods: Literature was synthesized in narrative form and in summary tables. Outcomes were categorized as: sexual function, reproductive hormones, fertility and pregnancy and offspring outcomes. Results are presented per category and per disease. Results: 9735 articleswere identified with our search strategy. After removal of duplicates, excluding articles by screening titles and abstracts and assessing eligibility by reading 289 fulltext articles, 87 articles fulfilled the eligibility criteria. All included studies enrolled patients diagnosed with a rheumatic disease and had results at least on one of the outcome categories. Sexual function was the most common category, followed by reproductive hormones, fertility and pregnancy and offspring outcomes. Sexual function is impaired in a high proportion of patients with rheumatic diseases. This was statistically significant in most of the studies where a control group was available. Clinically relevant abnormalities in reproductive hormones were mainly identified in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) and a positive correlation with disease activity were reported. Semen quality inmen with rheumatic diseases can be impaired in patients with SLE, SpA, sarcoidosis, BD and MWS. Sperm count and motility were the most common semen quality parameters affected. No negative effect of paternal RA and vasculitis on pregnancy outcomes were reported in 3 studies. No studies reporting the effect of paternal disease on offspring outcomes were identified. Limitations: Most of the studies included in this review suffer from an inconsistent methodological quality, definitions of outcomes varied in several studies, a wide variety of screening questionnaires and/or diagnostic tools were used and results might only apply to the specific populations that were studied. Conclusions: This systematic review suggests that sexual health is impaired in men with rheumatic diseases. The degree and extent of sexual health impairment vary per disease. More research is needed to fully understand the link between rheumatic diseases and impaired male sexual health. Meanwhile, rheumatologists should be aware of this association and discuss it with their patients. Implications of key findings: Sexual health of men with rheumatic diseases can be impaired by the disease itself. Especially in men trying to conceive, information on sexual function, reproductive hormones and sperm quality are needed to identify these problems. Treatment resulting in lower disease activity can improve overall sexual health in man with rheumatic diseases and facilitate their journey to fatherhood